Magnetic particle fingerprinting using COMPASS - Günther, J.; Kampf, T.; Rückert, M. A.; Friedrich, Bernhard; Reichl, T.; Tietze, Rainer; Lyer, Stefan; Alexiou, Christoph; Behr, V. C.; Vogel, P. (International Journal of Magnetic Particle Imaging, 2025)
To bring the application of magnetic nanoparticles (MNP) closer to application, reliable properties of a MNP suspension need to be ensured for reproducible quality and stability. This aims for a simple, robust and sensitive method that is able to assess the unique characteristics of MNP. We suggest Critical Offset Magnetic Particle SpectroScopy (COMPASS) as a suitable method for these needs, hence it allows for measuring a fingerprint characteristic for a unique MNP suspension. In the following, a dedicated fingerprinting routine to distinguish and classify different magnetic particle types will be introduced.
CRIS-Team Scopus Importer:2025-04-01